2020
DOI: 10.1029/2020gl089316
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Evidence for Crustal Modification Beneath the Hartford Rift Basin in the Northeastern United States

Abstract: Extensive Mesozoic rifting along the eastern North American margin formed a series of basins, including the Hartford basin in southern New England. Nearly contemporaneously, the geographically widespread Central Atlantic Magmatic Province (CAMP) was emplaced. The Hartford basin provides an ideal place to investigate the roles of rifting and magmatism in crustal evolution, as the integration of the dense SEISConn array and other seismic networks provides excellent station coverage. Using full‐wave ambient noise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 47 publications
0
28
1
Order By: Relevance
“…Interestingly, while there are lateral variations in the depth of the Moho converter across the SEISConn line, the amplitude of the converter appears to be relatively constant across the array (Figures 4 and 7). This finding is somewhat puzzling in light of previous results on the crustal velocity structure beneath SEISConn obtained via full-waveform ambient noise tomography (Gao et al, 2020). The model of Gao et al (2020) includes a high-velocity region in the lower crust beneath the Hartford Basin, which they attributed to the presence of high-density, high-velocity, likely mafic material in the lower crust, emplaced during the rifting that accompanied the breakup of Pangea, and associated with the Central Atlantic Magmatic Province (CAMP).…”
Section: Crustal Thickness and The Moho Stepmentioning
confidence: 68%
See 1 more Smart Citation
“…Interestingly, while there are lateral variations in the depth of the Moho converter across the SEISConn line, the amplitude of the converter appears to be relatively constant across the array (Figures 4 and 7). This finding is somewhat puzzling in light of previous results on the crustal velocity structure beneath SEISConn obtained via full-waveform ambient noise tomography (Gao et al, 2020). The model of Gao et al (2020) includes a high-velocity region in the lower crust beneath the Hartford Basin, which they attributed to the presence of high-density, high-velocity, likely mafic material in the lower crust, emplaced during the rifting that accompanied the breakup of Pangea, and associated with the Central Atlantic Magmatic Province (CAMP).…”
Section: Crustal Thickness and The Moho Stepmentioning
confidence: 68%
“…Gao et al. (2020) suggested that significant mafic magmatic underplating may have occurred beneath Hartford basin associated with the eruption of CAMP magmatism. We speculate that this addition of lower crustal material may have accompanied, and/or played a role in, alteration of the geometry of the crustal shear zone locally beneath Hartford basin.…”
Section: Discussionmentioning
confidence: 99%
“…Our model reveals strong structural variations within eastern North America. It has been demonstrated that more data and/or a more accurate methodology result in stronger velocity contrasts (e.g., Hung et al., 2004; Becker, 2012; Gao & Shen, 2014; Gao, 2018; Gao et al., 2020; Savage et al., 2017; Yang & Gao, 2020). Furthermore, we ignore seismic anisotropy and attenuation in wave simulation and inversion.…”
Section: Discussionmentioning
confidence: 99%
“…The Hartford basin (Figure 1) in central Connecticut formed in response to extension and exposes Mesozoic sedimentary, volcanic, and shallow intrusive rocks (Olsen, 1997). The volcanic and intrusive units are part of the geographically extensive Central Atlantic Magmatic Province (CAMP; e.g., Marzoli et al., 1999), and their emplacement was likely associated with modification of lower crustal structure beneath the Hartford basin (Gao et al., 2020). Parts of New England have been affected by post‐CAMP magmatic activity (e.g., Kinney et al., 2020), including the White Mountain Magma Series (WMMS) and Cretaceous magmatism in and around New Hampshire that may reflect the passage of the Great Meteor Hot Spot.…”
Section: Introductionmentioning
confidence: 99%
“…The Seismic Experiment for Imaging Structure Beneath Connecticut (SEISConn; Gao et al., 2020; Long & Aragon, 2020) was a deployment of 15 seismic stations across northern Connecticut and Rhode Island (Figure 2). SEISConn was designed as a high‐density array, with an average interstation distance of ∼10 km, and it enables the characterization of variations in shear wave splitting over short length scales beneath northern Connecticut, and the interrogation of the possible spatial relationships between anisotropy in the mantle lithosphere and major geologic and tectonic boundaries.…”
Section: Introductionmentioning
confidence: 99%